2014
DOI: 10.1515/jbcpp-2013-0141
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic and chlorogenic acids inhibit key enzymes linked to type 2 diabetes (in vitro): a comparative study

Abstract: The esterification of caffeic acid with quinic acid, producing chlorogenic acid, reduces their ability to inhibit α-amylase and α-glucosidase activities. Thus, the inhibition of α-amylase and α-glucosidase activities by the phenolic acids could be part of the possible mechanism by which the phenolic acids exert their antidiabetic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
150
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(180 citation statements)
references
References 27 publications
17
150
1
Order By: Relevance
“…Toshima et al (2010) found that a product made from fermented tea and loquat leaves had a better inhibitory effect on the α-glucosidase enzyme than the product made only with fermented tea leaves. Other reports have shown a significant role of certain phenolic compounds such as chlorogenic acid and flavonoids such as quercetin or its glycoside derivatives on the inhibition of α-amylase and α-glucosidase enzymes (Jo et al, 2009;Oboh et al, 2015). Therefore, the high inhibitory activity against evaluated key carbohydrate digestion enzymes observed in flower extracts may be partly due to their high chlorogenic acid and quercetin derivatives contents, which in turn also significantly contribute to their in vitro antioxidant capacity.…”
Section: α-Amylase α-Glucosidase and Ace-i Inhibitory Activities In mentioning
confidence: 97%
“…Toshima et al (2010) found that a product made from fermented tea and loquat leaves had a better inhibitory effect on the α-glucosidase enzyme than the product made only with fermented tea leaves. Other reports have shown a significant role of certain phenolic compounds such as chlorogenic acid and flavonoids such as quercetin or its glycoside derivatives on the inhibition of α-amylase and α-glucosidase enzymes (Jo et al, 2009;Oboh et al, 2015). Therefore, the high inhibitory activity against evaluated key carbohydrate digestion enzymes observed in flower extracts may be partly due to their high chlorogenic acid and quercetin derivatives contents, which in turn also significantly contribute to their in vitro antioxidant capacity.…”
Section: α-Amylase α-Glucosidase and Ace-i Inhibitory Activities In mentioning
confidence: 97%
“…Moreover, Caffeic and chlorogenic acids reduce the ability to inhibit α-amylase and α-glucosidase activities and therefore lead to anti-diabetic effects [19]. Researchers also considered caffeic and chlorogenic acids as promising agents for treating human breast cancer, head and neck squamous, lung and cervical carcinoma cells [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…There are experimental studies on animal model, that have showed the inhibitory potential of ginger on other targets, which include; acetylcholinesterase in relevance to Alzheimer's disease [12], angiotensin-1 converting enzyme (ACE) and arginase in relevance to hypertension and atherosclerosis respectively [13,14], α-glucosidase in relevance to type-2 diabetes [15]. The result of these studies indicated moderate inhibition of the targets by ginger extract, which were similar to the report of Sanghal et al [16].…”
Section: Discussionmentioning
confidence: 99%